2014
DOI: 10.7860/jcdr/2014/7516.4007
|View full text |Cite
|
Sign up to set email alerts
|

Role of Gender and Serum Immunoglobulin E (IGE) levels on Severity of Migraine

Abstract: Prevalence of migraine is high among females. Younger age and female sex are other contributory factors as prevalence of migraine is higher in these groups. Degree of allergic sensitisation determines the severity and frequency of headaches in those whom allergic rhinitis is a risk factor as evidenced by higher levels of IgE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Abramson) based on a previous study that correlated allergic sensitization characterized by high blood levels of IgE with greater disability due to headache in 100 migraine patients 18 .…”
Section: Statisticsmentioning
confidence: 99%
“…Abramson) based on a previous study that correlated allergic sensitization characterized by high blood levels of IgE with greater disability due to headache in 100 migraine patients 18 .…”
Section: Statisticsmentioning
confidence: 99%
“…Similarly, in a prospective study, Theodoropoulos et al [ 58 ] observed that interictal serum C-reactive protein levels declined and the severity of migraines and rhinitis decreased during sublingual immunotherapy. Immunotherapy induces tolerance to specific allergens through two mechanisms of action: by altering cytokine responses of T helper cells and by promoting IgG and IgA, antibodies that block the binding of IgE to mast cells [ 59 61 ]. Data from another study revealed a correlation between serum IgE levels and the severity and frequency of migraines: patients with higher levels of IgE had more severe headaches than those with lower levels of IgE [ 61 ].…”
Section: Comorbidity and Pathophysiologymentioning
confidence: 99%
“…Immunotherapy induces tolerance to specific allergens through two mechanisms of action: by altering cytokine responses of T helper cells and by promoting IgG and IgA, antibodies that block the binding of IgE to mast cells [ 59 61 ]. Data from another study revealed a correlation between serum IgE levels and the severity and frequency of migraines: patients with higher levels of IgE had more severe headaches than those with lower levels of IgE [ 61 ]. These data support the hypothesis that migraine severity and disability depend on coexisting allergic rhinitis, which might provide an interesting rationale for treatments targeted at reducing migraine intensity and disability among patients with coexisting allergy and migraine; however, further investigation is needed.…”
Section: Comorbidity and Pathophysiologymentioning
confidence: 99%
“…No patient declined participation during the period of this research, which was conducted in accordance with the Declaration of Helsinki and was approved by the Ethical Committee of Universidade de Passo Fundo on October 18, 2016 (report number 1.779.204). Sample size was estimated with the aid of software WinPepi version 11.50 (J. H. Abramson) based on previous results from Rosario and Pinto who correlated allergic sensitization characterized by high blood levels of IgE with greater disability due to headache in 100 migraineurs 19 .…”
Section: Methodsmentioning
confidence: 99%
“…Such rich inflammatory processes that take place in allergic rhinitis could theoretically predispose the patient to migraine worsening, not only through cephalic nociceptive pathways, but also by triggering an immune response not necessarily restricted to the head. For example, allergic sensitization measured by serum immunoglobulin E (IgE) has already been linked to aggravated migraine in adults 19 .…”
mentioning
confidence: 99%